2012
DOI: 10.5194/cp-8-1457-2012
|View full text |Cite
|
Sign up to set email alerts
|

Investigating late Holocene variations in hydroclimate and the stable isotope composition of precipitation using southern South American peatlands: an hypothesis

Abstract: Abstract. Ombrotrophic raised peatlands provide an ideal archive for integrating late Holocene records of variations in hydroclimate and the estimated stable isotope composition of precipitation with recent instrumental measurements. Modern measurements of mean monthly surface air temperature, precipitation, and δD and δ 18 O-values in precipitation from the late twentieth and early twenty-first centuries provide a short but invaluable record with which to investigate modern relationships between these variabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
0
6
0
2
Order By: Relevance
“…El calentamiento del clima patagónico cuyo efecto más directo es el retroceso generalizado de los glaciares al S de los 45° S de latitud y específicamente en el CHN, ha sido relacionado con un desplazamiento persistente al S de los vientos del W durante el verano y el otoño austral, asociado con una fase positiva del Modo Anular del Sur, posterior a la PEH (Daley et al, 2012;Moreno et al, 2014); con el aumento significativo de las temperaturas mínimas a partir de la segunda mitad del siglo XX, particularmente después del cambio de régimen del Indice de Oscilación del Sur en 1976 (Rosenbluth et al, 1997) y con los cambios en la Oscilación Decadal del Pacífico, que influyen desde 1976 en el clima patagónico, elevando las temperaturas medias de verano, particularmente en las altas latitudes (Villalba et al, 2003).…”
Section: Las Variaciones Climáticas Decadales Post Pehunclassified
See 1 more Smart Citation
“…El calentamiento del clima patagónico cuyo efecto más directo es el retroceso generalizado de los glaciares al S de los 45° S de latitud y específicamente en el CHN, ha sido relacionado con un desplazamiento persistente al S de los vientos del W durante el verano y el otoño austral, asociado con una fase positiva del Modo Anular del Sur, posterior a la PEH (Daley et al, 2012;Moreno et al, 2014); con el aumento significativo de las temperaturas mínimas a partir de la segunda mitad del siglo XX, particularmente después del cambio de régimen del Indice de Oscilación del Sur en 1976 (Rosenbluth et al, 1997) y con los cambios en la Oscilación Decadal del Pacífico, que influyen desde 1976 en el clima patagónico, elevando las temperaturas medias de verano, particularmente en las altas latitudes (Villalba et al, 2003).…”
Section: Las Variaciones Climáticas Decadales Post Pehunclassified
“…La tendencia general en el sector es a evolucionar hacia periodos más secos, al igual que en el resto de Patagonia (Rasmussen et al, 2007;Masiokas et al, 2008;Neukom et al, 2010;Daley et al, 2012). Durante la primera parte del siglo XX, las precipitaciones están por sobre la media culminando en 1950, luego disminuyen las precipitaciones de invierno (Figura N° 14a).…”
Section: Las Variaciones Climáticas Decadales Post Pehunclassified
“…They have only sparse data points for southernmost South America, whereas our reconstructions extend the evidence for (late) 17 th Century dryness, further south into Tierra del Fuego. Daley et al (2012) noted that Ushuaia (see Fig. 1) has in recent decades been getting wetter over the instrumental period in response to intensification and southward movement of the Westerlies.…”
Section: Relationship To Previous Workmentioning
confidence: 99%
“…Nevertheless, the datasets reported here indicate that the greatest inferred climatic deviations fit well with climate excursions elsewhere, even though it is assumed that the principal change in the mire relates to bog surface wetness, rather than to temperature. Further work might be directed to investigating deuterium excess, as suggested in Daley et al (2012), which could help to show whether shifting Westerlies were indeed the mechanism for inferred changes in bog surface wetness at this site.…”
Section: Limitations To the Proxy-climate Measuresmentioning
confidence: 99%
“…Moreover, rather than a north-south orientation, the Andean divide in Tierra del Fuego has a northwest-southeast orientation which may attenuate the rain shadow effect to the northeast. Considering the orographic complexity of southern Patagonia, Daley et al (2012) suggested relatively important intra-regional differences in moisture source for precipitation between Punta Arenas and Ushuaia at decadal timescales.…”
Section: Introductionmentioning
confidence: 99%